DIFFERENCES BETWEEN HYDROCARBON CONTROL CONCEPTS STAD TYPE COOPERATIVE LEARNING MODEL ACCOMPANYING PROBLEM POSING WITH STRATEGY CONVENTIONAL LEARNING - Joni Saputra; Tasviri Efkar; Ila Rosilawati (Universitas Lampung, 2012)
The study aims to describe (1) the existence of the average difference between the value of mastery of concepts hydrocarbon type STAD cooperative learning model along with problem posing strategies with conventional learning, (2) the average value of mastery of concepts which higher hydrocarbons between cooperative learning model types STAD with problem posing strategies with conventional learning. The population in this study were all students of class X SMAN 13 Bandar Lampung academic year 2011/2012. Sampling was done by purposive sampling. The samples in this study were 30 students of class X1 as a class experiment 1 and 30 X7-class students as a class experiment 2. The study design used was The Matching-Only Posttest-Only Control Group Design. The results showed that (1) there is a difference between the students 'mastery of concepts Hydrocarbon type STAD cooperative learning strategies with problem posing and conventional learning and (2) the average students' mastery of concepts Hydrocarbons using STAD cooperative learning model type with problem posing strategy is higher than the average student mastery of concepts in hydrocarbon material using conventional learning.Keywords: type STAD cooperative learning strategies with problem posing, conventional learning, mastery of concepts